Partisipasi Masyarakat Dalam Pembangunan Kota yang Berkelanjutan dan Berkeadilan - Asep Warlan Yusuf (Jurnal Administrasi Publik, 2014)
Since independence until now, the of public law, especially in the field of Indonesian administrative law, has not been able to serve as reinforcement in community empowerment and things connected with public control over the government. Empirically, it is evident, that the implementation of development activities requires at least five conditions simultaneously engaged in achieving the ultimate goal of equitable public welfare. The respective requirements are the rule of law and human rights; democratic governance, equitable laws, material, and non-material aspects of development, and a more genuine community empowerment.This article tries to necessitate, firstly, that the development activities cannot be carried out by ignoring each other of any such conditions. Secondly, it is a warning the failure to achieve the planned development goals in the result of a partial way of thinking, both at the level of policy formulation as well as its implementation. In addition, to eliminate the adverse impact on the implementation of the general welfare, development must be based on a development policy that is oriented to human development which requires wider participation of a people. That is, the main focus of planning humans in the development, in addition to having ethical arguments. Also has legal dimensions in the level of its implementation.